Coupling shifts in the composition of coral tissue- and mucusassociated microbial communities to changes in coral host physiology and environmental fluctuations - Marchioro, Giulia Manso (2021)
Understanding the drivers of microbiome variation in corals is crucial to better predict the effects of environmental pressures on coral holobionts and coral reef ecosystems. However, much remains to be understood about corals and the interactions they establish with microorganisms. My hypothesis is that the microbiome of the surface mucus layer (SML) is mainly influenced by environmental parameters due to its direct contact with the environment, whereas the tissue microbiome is more driven by the physiology of the coral host. Therefore, the aim of the present work is to distinguish the effect of the host’s intrinsic and environmental factors on the microbiome composition in different coral compartments (SML and tissue), and to identify possible overarching trends in the environmental sensitivity of distinct microbiomes within a coral holobiont. Using next-generation amplicon-sequencing of the 16S rRNA gene, the analyses showed that microbiomes of Acropora spp. differed significantly between compartments (SML versus tissue) and species (A. tenuis versus A. millepora), but also among sampling location and season. Seawater samples were characterized by dominance of members of the Synechococcaceae and Pelagibacteraceae. In Acropora spp., mucus microbiome was dominated by members of Flavobacteriaceae, Synechococcaceae, Rhodobacteraceae and Pelagibacteraceae families, while the tissue microbiome was dominated by the Endozoicimonaceae family. SML microbiomes of both coral hosts correlated best with environmental parameters as ammonium, total suspended solids, particulate organic carbon, number of raindays and nitrate/nitrite. However, the amount of influence from environmental parameters on the mucus (explaining 12-15% of variation) is relatively low as compared with the influence of those parameters on the seawater microbiome (explaining 49% of variation). In contrast, the tissue microbiomes of the two Acropora species showed distinct and species-specific responses to environmental and physiological parameters, suggesting host-specific modulation of the environmental drivers of the tissue microbiome.